The Effect of Shear Stress on the Size, Structure, and Function of Human von Willebrand Factor. Issue 9 (September 2014) - Chan, Chris Hoi Houng; Pieper, Ina Laura; Fleming, Scott; Friedmann, Yasmin; Foster, Graham; Hawkins, Karl; Thornton, Catherine A.; Kanamarlapudi, Venkateswarlu
Abstract Clinical outcomes from ventricular assist devices (VADs) have improved significantly during recent decades, but bleeding episodes remain a common complication of long‐term VAD usage. Greater understanding of the effect of the shear stress in the VAD on platelet aggregation, which is influenced by the functional activity of high molecular weight (HMW) von Willebrand factor (vWF), could provide insight into these bleeding complications. However, because VAD shear rates are difficult to assess, there is a need for a model that enables controlled shear rates to first establish the relationship between shear rates and vWF damage. Secondly, if such a dependency exists, then it is relevant to establish a rapid and quantitative assay that can be used routinely for the safety assessment of new VADs in development. Therefore, the purpose of this study was to exert vWF to controlled levels of shear using a rheometer, and flow cytometry was used to investigate the shear‐dependent effect on the functional activity of vWF. Human platelet‐poor plasma (PPP) was subjected to different shear rate levels ranging from 0 to 8000/s for a period of 6 h using a rheometer. A simple and rapid flow cytometric assay was used to determine platelet aggregation in the presence of ristocetin cofactor as a readout for vWF activity. Platelet aggregates were visualized by confocal microscopy. Multimers of vWF were detected using gel electrophoresis and immunoblotting. The longer PPP was exposed to high shear, the greater the loss of HMW vWF multimers, and the lower the functional activity of vWF for platelet aggregation. Confocal microscopy revealed for the first time that platelet aggregates were smaller and more dispersed in postsheared PPP compared with nonsheared PPP. The loss of HMW vWF in postsheared PPP was demonstrated by immunoblotting. Smaller vWF platelet aggregates formed in response to shear stress might be a cause of bleeding in patients implanted with VADs. The methodological approaches used herein could be useful in the design of safer VADs and other blood handling devices. In particular, we have demonstrated a correlation between the loss of HMW vWF, analyzed by immunoblotting, with platelet aggregation, assessed by flow cytometry. This suggests that flow cytometry could replace conventional immunoblotting as a simple and rapid routine test for HMW vWF loss during in vitro testing of devices.